Is there any relationship between physical activity level and patterns, and physical performance in children? - Blaes Aurélie; Baquet Georges; Fabre Claudine; Van Praagh Emmanuel; Berthoin Serge (BMC, 2011)
Abstract Background It is often assumed that physical activity (PA) and physical performance during childhood and adolescence are beneficial for health during adulthood, but a positive relationship between PA and physical performance has not been precisely clarified in children. The lack or the weakness of the relationships between PA and physical performance could be due to the measure of PA. If the use of accelerometry is considered as an objective and common measure of PA, the real patterns of children's habitual PA must be reflected. The aim of this study was to investigate the relationship between the levels and patterns of PA assessed with high frequency accelerometry and physical performance in young children. Methods Eighty-six boys and 101 girls aged 6-12 years participated in this study. Physical activity was measured over a 7-day period, using a 5-s epoch. Physical performance was assessed by means of EUROFIT tests (anthropometrics, standing broad jump, the 10 × 5 meter shuttle run, the sit-and-reach, the handgrip, the number of sit-ups in 30 seconds, the 20-meter shuttle run). Results No relationship was found between PA and physical performance. In boys only, body fatness was negatively associated with vigorous PA (r = -0.38, p < 0.001) and very high PA (r = -0.35, p < 0.01), in contrast to light PA (r = 0.28, p < 0.01), which was positively related to body fatness. Conclusion In 6- to- 12 year- old children, the more active children were not the fittest. Our results also underline the need for uniformity in approach to measurement of PA, body composition and health-related fitness between studies.